2001
DOI: 10.1177/107110070102201007
|View full text |Cite
|
Sign up to set email alerts
|

Crescentic Proximal Metatarsal Osteotomy for Moderate to Severe Hallux Valgus: A Mean 12.2 Year Follow-Up Study

Abstract: The senior author's (R.C.) first 25 patients (37 feet) treated with a combination proximal crescentic osteotomy and distal soft-tissue reconstruction made up the patient cohort. All 25 patients were reviewed at a minimum of one year post-op (short-term follow-up) and 20/25 (31/37 feet) were reviewed again at a mean 12.2 years (range 11.4 to 13.0 yrs) post-op (long-term follow-up). This allowed for a comparison of short- and long-term results and led to a long-term follow-up rate of 84% (31/37 feet, mean 12.2 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
94
4
25

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(130 citation statements)
references
References 14 publications
7
94
4
25
Order By: Relevance
“…The second limitation of this study is that the follow-up period was short; the results may change if we had followed the patients for a longer time. However, previous studies have compared one-year radiographic results with longer-term results and concluded that results did not change after one year [28,29]. Hallux valgus angle and the intermetatarsal angle stabilised at six months after surgery in the K-wire group, although the sesamoid position continued to deteriorate in this study.…”
Section: Discussioncontrasting
confidence: 46%
“…The second limitation of this study is that the follow-up period was short; the results may change if we had followed the patients for a longer time. However, previous studies have compared one-year radiographic results with longer-term results and concluded that results did not change after one year [28,29]. Hallux valgus angle and the intermetatarsal angle stabilised at six months after surgery in the K-wire group, although the sesamoid position continued to deteriorate in this study.…”
Section: Discussioncontrasting
confidence: 46%
“…Degenerative changes of the metatarsophalangeal joint increased at follow-up and were grade 2 or 3 in 20% of the cases. The same observation has been reported by others [5,8,14]. The average AOFAS score at follow-up was 87, and 86% of the results were excellent or good; 94% of the patients felt that the results of the operation were satisfactory or satisfactory with reservations.…”
Section: Discussionsupporting
confidence: 79%
“…The crescentic osteotomy originally described by Mann et al [5] has been widely used [8,[10][11][12][13][14]. This series represents our initial experience with the distal soft tissue realignment and proximal crescentic metatarsal osteotomy.…”
Section: Discussionmentioning
confidence: 95%
“…Rarely, also young people and children can be affected by this condition [4]. Several authors have tried to assess pathogenesis and risk factors, which include biomechanical, genetic and familial factors [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]; however, the end point is impairment of the normal function of the first metatarsophalangeal joint. Clinical symptoms include pain and reduced range of motion of the first metatarsophalangeal joint, where bursitis or callosities are often present.…”
Section: Introductionmentioning
confidence: 99%